A novel endobronchial approach to massive hemoptysis complicating silicone Y-stent placement for tracheobronchomalacia: A case report. Issue 8 (February 2018) - Ryu, Changwan; Boffa, Daniel; Bramley, Kyle; Pisani, Margaret; Puchalski, Jonathan
Abstract: Rationale: Airway stabilization for severe, symptomatic tracheobronchomalacia (TBM) may be accomplished by silicone Y-stent placement. Common complications of the Y-stent include mucus plugging and granulation tissue formation. Patient concerns: We describe a rare case of massive hemoptysis originating from a silicone Y-stent placed for TBM. Diagnoses: An emergent bronchoscopy showed an actively bleeding, pulsatile vessel at the distal end of the left bronchial limb of the Y-stent. It was felt that the bleeding was caused by, or at least impacted by, the distal left bronchial limb of the Y-stent eroding into the airway wall. Interventions: We hypothesized that placement of oxidized regenerated cellulose (ORC) would provide initial hemostasis, and the subsequent placement of a biocompatible surgical sealant would lead to definitive resolution. Outcomes: ORC provided sufficient hemostasis and the subsequent synthetic polymer reinforced the tissue for complete cessation of the bleed. Lessons: The combined use of ORC and a biocompatible surgical sealant provided long-term management for life-threatening hemoptysis, and potentially morbid procedures such as embolization or surgery were avoided by advanced endobronchial therapy.